A structural equation model of posttraumatic growth after prostate cancer. Issue 11 (15th April 2014) - Wilson, Bridget; Morris, Bronwyn A.; Chambers, Suzanne
Abstract Background Posttraumatic growth (PTG) encompasses an individual's perception of positive personal changes as a consequence of a traumatic incident. The current study tested a theoretical model of PTG with the inclusion of resilience in the context of cancer survivors. Methods Members of a prostate cancer support network were invited to complete a cross‐sectional mail survey (N = 514, 52.8% response; mean age 70.17 years, and time since diagnosis 7.5 years). Results Challenge appraisal (β = 0.361), examining core beliefs (β = 0.474), intrusive rumination (β = 0.130), and peer support factors (β = 0.104) had significant direct effects on PTG. Resilience (β = 0.164), challenge appraisal (β = 0.215), distress (β = 0.186), and examining core beliefs (β = 0.105) had significant indirect effects on PTG. Conclusions Results support the notion that the appraisal of cancer, disruption of fundamental beliefs, and experience of intrusive cancer‐related rumination are associated with PTG. Additionally, a sense of connection with peers and seeking an understanding of the cancer experience through peers is important for the perception of PTG. Possible indirect pathways were also proposed between resilience and PTG. Copyright © 2014 John Wiley & Sons, Ltd.